Macro Policy Lessons for a Sound Design of Fiscal Decentralization-Background Studies. (Policy Papers; Policy Paper ;, 2009)
This paper provides background to the Board paper on Macro Policy Lessons for a Sound Design of Fiscal Decentralization. It summarizes the findings and recommendations of the Fiscal Affairs Department (FAD) for ten countries to which it provided advice on fiscal decentralization. The selected countries (Bolivia, People's Republic of China, Colombia, Democratic Republic of Congo, Indonesia, Kosovo, Liberia, FYR Macedonia, Mexico, and Nigeria) represent different regions, varying institutional arrangements, and diverse stages of the decentralization process.